Implementation of environmental management elements in accommodation facilities in Prague - Vizilo, Ksenia (2024)
The aim of this thesis was to investigate the implementation of environmental management elements in accommodating facilities in selected area. It sought to assess the current status of environmental management practices within these facilities and provide recommendations for improvement. In the first, theoretical, part of the thesis, the concept of environmental management, its application along with advantages and disadvantages, as well as the certification of accommodation facilities, were explained. Specific elements of environmental management were also discussed and analyzed in the second, subsequent, part of the thesis. The research methodology involved a questionnaire, which allowed for a comprehensive examination of environmental practices and was designed to evaluate the environmental measures implemented in accommodation facilities. The questions addressed ways to save electricity, water and heating, as well as regulating the consumption of plastic and paper, waste sorting, the use of environmentally friendly cleaning agents and products, renewable sources and ultimately, motivating hotel employees to protect the environment. The results revealed that despite existing practices, current measures are insufficient to achieve a significant reduction in the negative impact of the hotel business on the environment.